Rancang Bangun Sistem Informasi Persediaan Access Point Pada PT Telekomunikasi Indonesia Divisi Regional V - Putra, Wahyu Septiono Asmara; Supriyanto, Antok; Sukmaaji, Anjik (Jurnal Sistem Informasi Universitas Dinamika (JSIKA), 2017)
Access Point is a program of PT Telekomunikasi Indonesia in the field of improving the acceleration and expansion of Indonesia's economy, and also aims to catch up with technological development in Indonesia with other countries. Pengelolaann process inventory at Telkom access point that often occurs deficiencies and therefore can not serve the replacement of the access point that is damaged.To solve problems related to inventory access point then made the inventory information system access point. The system uses a method Reorder Point (ROP) to overcome supply shortage access point. The system includes recording made damaged access point, the access point ROP calculation and booking access point.Results of testing the inventory information system created access point can help facilitate Telkom Regional Division V to manage access point. With this system can connect Telkom Regional Division V and Witel, with this access point management processes that previously have run out will be resolved by this system. In addition to the online system then management can access the system through some gadgets, such as the monitoring of the status of the access point, the calculation of ROP, and booking access point.